PEMBERDAYAAN PENDIDIKAN AGAMA ISLAM BERBASIS TRADISI NU DI PESANTREN KABUPATEN JEPARA: Studi Kasus Pada Pesantren Ummul Quro Pecangaan - Adhim, Amrul; Darnoto, Darnoto (Borneo : Journal of Islamic Studies, 2025)
This study aims to analyze the empowerment strategies of Islamic religious education based on Nahdlatul Ulama (NU) traditions in Islamic boarding schools (pesantren) in Jepara Regency especially on Ummul Quro boarding schools Pecangaan as well as to identify the supporting and inhibiting factors in the process. Employing a descriptive qualitative approach, data were collected through in-depth interviews, participatory observation, and documentation studies, then analyzed using triangulation techniques to enhance the validity of the findings. The results show that pesantren in Jepara have integrated NU traditional values into education through habitual religious activities such as tahlilan, manaqiban, yellow book (kitab kuning) studies, and moral education. Additionally, some pesantren have begun implementing economic empowerment programs through local-based entrepreneurship training. The main supporting factors for this empowerment are the strong local culture rooted in NU traditions and the central role of kyai in pesantren life. Identified inhibiting factors include limited infrastructure, a lack of professional educators, and low utilization of modern technology in the learning process. The study concludes that, despite the significant potential of NU-based pesantren in Jepara as agents of transformation in Islamic religious education, efforts to innovate curricula, strengthen human resource capacity, and optimize technology utilization are urgently needed to enhance empowerment effectiveness. Collaboration between pesantren, the government, and religious organizations is necessary to address these challenges and strengthen the contribution of pesantren to community development based on moderate Islamic values.